Analisis Perbedaan Pendapatan Petani Kopi (Pola Diversifikasi dan Non-Diversifikasi) di Kecamatan Atu Lintang Kabupaten Aceh Tengah - Fahira Leny Alansa; Mustafa Usman; Widyawati Widyawati (Fakultas Pertanian, Universitas Syiah Kuala, 2022)
The problem of the selling price of coffee beans cannot be separated from dependence on export markets which are more vulnerable and risky when compared to commodities that have alternative market shares such as the domestic market. The occurrences is often detrimental to farmers, because the harvest is the time that is awaited, especially for farmers in Atu Lintang. This is because almost all people are coffee farmers who are very dependent on the production and selling price of coffee. Presence of diversification plants on the same land as coffee can provide oppotunities for new sources of income for farmers and an reduce price fluktuations and crop failures in one of the commodities that can harm farmers. Where in addition to coffee, farmers divesify their coffee plants with fruit tree in the form of avocados, oranges, and bananas. But in Atu Lintang not all farmers implement diversification. There are still many farmers who only grow coffee plants. This study aims to find out how the differences in farm income that apply a diversification pattern and non-diversification farming pattern in Atu Lintang sub district. In this study using two average difference test analysis or independent sample t-test. The analytical method used is statistical analysis of the average differences test or independent sample t-test. The results showed that the income of the diversification farming pattern was greater than that of the non-diversification farming pattern. This is indicated by the results of the independent sample t-test where the t-count value obtained is greater than the t-table, which is 3.082 2.019 at the 95% confidence level.